2019
DOI: 10.3390/nano9040554
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Views of Atomic and Molecular Oxygen Bonding with epi Ge(001)-2 × 1 Studied by High-Resolution Synchrotron Radiation Photoemission

Abstract: In this paper, we investigate the embryonic stage of oxidation of an epi Ge(001)-2 × 1 by atomic oxygen and molecular O2 via synchrotron radiation photoemission. The topmost buckled surface with the up- and down-dimer atoms, and the first subsurface layer behaves distinctly from the bulk by exhibiting surface core-level shifts in the Ge 3d core-level spectrum. The O2 molecules become dissociated upon reaching the epi Ge(001)-2 × 1 surface. One of the O atoms removes the up-dimer atom and the other bonds with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(82 reference statements)
1
3
0
Order By: Relevance
“…22. Two facts are pertinent here: the first is that the resolved energies including the bulk and the three surface-related components are similar to those given in a previous report of epi Ge(001)-2 × 1, 22,31) and the second is that no additional component is required to reproduce the Ge 3d line shape.…”
supporting
confidence: 70%
“…22. Two facts are pertinent here: the first is that the resolved energies including the bulk and the three surface-related components are similar to those given in a previous report of epi Ge(001)-2 × 1, 22,31) and the second is that no additional component is required to reproduce the Ge 3d line shape.…”
supporting
confidence: 70%
“…3 does not follow the O 2 reactions on epi Ge(001)-2 × 1. 30,31) Instead, the O 2 atoms are dissociated after impinging the epi Ge(001) surface. One ion removes the up-dimer Ge atom from the surface and the other bonds with the underlying Ge atom in the subsurface layer.…”
mentioning
confidence: 99%
“…It is composed by eight research articles, that together provide not only an interesting and multi-disciplinary overview on the chemico-physical investigation of nanostructured materials carried out by state-of-the-art synchrotron radiation induced techniques, but also an exciting glance on the future perspectives of nanomaterials characterization methods. The published papers focus on the chemical, structural, and morphological characterization of nanostructured materials of different nature carried out by a wide selection of SR-induced techniques such as the X-ray photoelectron spectroscopy (XPS) [1,2] and near edge X-ray absorption fine structure (NEXAFS) [1], in situ XPS and electrochemistry [3], time-resolved X-ray scattering [4], nuclear forward scattering (NFS) of synchrotron radiation [5], soft X-ray absorption spectroscopy (sXAS) [6], X-ray fluorescence [7], X-ray diffraction [7], X-ray absorption [7] and time-resolved X-ray transmission microscopy [8].…”
mentioning
confidence: 99%
“…In the first paper of the Special Issue [1] V. Secchi et al exploited an SR-induced XPS and angular dependent NEXAFS to investigate the chemisorption of a self-assembling peptide (EAbuK16, i.e., H-Abu-Glu-Abu-Glu-Abu-Lys-Abu-Lys-Abu-Glu-Abu-Glu-Abu-Lys-Abu-Lys-NH 2 ) onto annealed Ti25Nb10Zr alloy surfaces; the data acquired on Ti25Nb10Zr discs after incubation with self-assembling peptide solution at five different pH values allowed the investigation of the best conditions for peptide immobilization, by comparing the quality (coverage, molecular order) of the obtained nanostructured films. The X-ray photoemission spectroscopy at a high resolution, allowed by the use of SR as an X-ray source, was also exploited in the work from Y.-T. Cheng et al [2] to investigate the embryonic stage of oxidation of an epi Ge(001)-2 × 1 by atomic oxygen and molecular O 2 . The authors observed that the topmost buckled surface with the up- and down-dimer atoms, and the first subsurface layer behaved distinctly from the bulk by exhibiting surface core-level shifts in the Ge 3d core-level spectrum, and that O 2 molecules underwent dissociation upon reaching the epi Ge(001)-2 × 1 surface.…”
mentioning
confidence: 99%